USE OF SEDIMENTATION TANKS TO LOWER BOD LEVEL IN TOFU LIQUID WASTE - Manguju, Mamiek Oktrina; La Taha, La Taha; Erlani, (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Home tofu industry is one of the small-scale industries that still very rarely have waste disposal installations where liquid waste tofu is mostly dumped directly into the environment and water bodies. Liquid waste tofu produced containing Total Suspended Solid (TSS), Chemical Oxygen Demand (COD) And High Biochemical Oxygen Demand (BOD) can result in environmental damage and impact on health.This study aims to lower BOD levels in tofu liquid waste by using anaerobic sedimentation ponds with a variation in the retention time of 24 hours, 28 hours and 32 hours. The research used is Quasi-Experimentation. The total samples of liquid wastewater tofu used as much as 90 liters are divided in three sedimentation tanks with the amount of each treatment 3 times replication.The results showed that bod levels of liquid waste home tofu after processing with sedimentation ponds in an anaerobic state with a 24-hour stay examination of initial BOD levels of 325.5 mg / l after processing 297 mg / l with a percentage of 9%, at the examination of 28 hours the initial level of 325.5 mg /l after processing 267 mg / l with a percentage of 18.13% and examination 32 hours the initial level of BOD 325.5mg / l dropped to 200.3 with a percentage of 39%.The conclusion of this study is the use of sedimentation room with a variation in the time of stay able to lower bod levels up to 39%, but has not met the requirements of Governor Sul-Sel Regulation No.69 year 2010 on Quality Standards and Environmental Damage Criteria.